Large Foreign Body as a Nidus for a Common Duct Stone in a Patient Without Spontaneous Biliary Enteric Fistula or Previous Abdominal Surgery. Issue 3 (1993) - Cetta, Francesco; Lombardo, Francesco; Rossi, Stelio
Abstract : We report a case of a brown pigment gallstone, which formed around a phytobezoar in the common bile duct, in a patient without spontaneous biliary enteric fistula or previous abdominal surgery. A brief comment on the possible origin of the phytobezoar in this case and on the pattern of deposition of brown material over a pre-existent nidus is also presented.